Unveiling the toxicity of JWH-018 and JWH-019: Insights from behavioral and molecular studies in vivo and vitro - Fenghua Zhou; Yan Shi; Sujun Tan; Xiaoli Wang; Weicheng Yuan; Shuqi Tao; Ping Xiang; Bin Cong; Chunling Ma; Di Wen (Ecotoxicology and Environmental Safety)
Due to the structural diversity and rapid prevalence of synthetic cannabinoids (SCs) in the market, the information linking the chemical structure of SCs to their toxicity remains scant, despite emerging in the 1970s. In the present study, we aimed to investigate the toxicity and underlying mechanisms of indole SCs JWH-018 and JWH-019 in mice (C57BL/6, male, 6–8 weeks old), zebrafish (AB strain, male, 4–5 months old) and modified human embryonic kidney (HEK) 293 T cells, using behavioral, pharmacokinetic, pharmacological approaches, and molecular docking. JWH-018 induced time- and dose-dependent cannabinoid-like effects in mice (administration dosages: 0.02, 0.1, and 0.5 mg/kg, i.p.), and yielded dose-dependent anxiogenic effects and lower aggression behavior in zebrafish (administration dosages: 0.01, 0.05, and 0.25 µg/g, i.p.), unlike JWH-019. These effects were blocked by the selective cannabinoid receptor 1 (CB1R) antagonist AM251. JWH-018, but not JWH-019, activated the CB1R-dependent extracellular signal-regulated kinase 1 and 2 (ERK1/2) pathway in vivo and in vitro. Molecular docking identified essential residues PHE268, PHE170, and TRP279 within CB1R as pivotal contributors to enhancing receptor-ligand associations. While both drugs had a similar binding pattern with shared linker binding pockets in CB1R, there were still differences in their spatial conformation. These findings shed light on the molecular pharmacology and activation mechanism of SCs for CB1R and should guide further research into the mechanisms underlying their deleterious effects in humans.